Pengaruh Perubahan Buah Jambu Biji (Psidium Guajava L) Selama Penyimpanan dalam Suhu Rendah dengan Metode Pembungkusan - Dimas Pratama; Desi Sri Pasca Sari Sembiring; Maimunah Siregar; Mohd. Syaifudin Bin Abdul Rahman (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
This study aimed to determine the effect of packaging methods on the quality of guava fruit (Psidium guajava L.) during low-temperature storage. The research was conducted at the Horticulture Laboratory of the Malaysian Agricultural Research and Development Institute (MARDI), Malaysia, from July to August 2025. The research method used was an experimental approach with five packaging treatments, namely T1 (PP650 without MAP), T2 (PP650 + MAP PP), T3 (PP650 + MAP PE), T4 (vacuum packaging PP), and T5 (450-micron MAP seal). The observed parameters included fruit weight, pH, malic acid content, tartaric acid content, and fruit size on day 0, day 4, day 8, and day 12 of storage. The results showed that packaging methods affected the quality of guava fruit during low-temperature storage. The treatment without MAP experienced a faster decline in quality, indicated by an increase in pH, a decrease in organic acid content, and fruit weight loss. In contrast, MAP and vacuum packaging treatments were able to maintain fruit weight, acid content, and fruit size better until the 12th day of storage. Treatment T2 (PP650 + MAP PP) and T3 (PP650 + MAP PE) showed the best results in maintaining fruit quality compared to the other treatments. Based on the results of this study, the use of MAP and vacuum packaging methods is recommended for guava storage because they can slow down quality deterioration and extend the shelf life of the fruit, which aligns with recent parameters of low-temperature fruit handling (Chen et al., 2024; Etemadipoor et al., 2020; Fan et al., 2022).